Endangered Dracaena ombet Population in the Red Sea Hills, Sudan, Recovers After Abrupt Change - Andersen, Gidske L.; Krzywinski, Knut; Talib, Mohammed; Musa, Mohammed A. M. (Frontiers in Environmental Science, 2022)
The endangered and endemic Nubian dragon blood tree, Dracaena ombet, has been feared extirpated from core distribution areas in the Red Sea Hills, Sudan, after reported mass death events in the 20th century. Populations of Dragon tree species are generally reported to be in decline, with a noticeable lack of recruitment and possible poor resilience. Rare recruitment events are, however, normal for species with remnant population dynamics, and when eventually occurring, such events can restore seemingly degraded populations. In response to recently reported observations of dracaena saplings in a historically core distribution area of the Red Sea Hills, we assess the status of this long-lived arboreal species. We describe a current realized niche, investigate a potential range shift by comparing the spatial distribution of saplings and older individuals, and assess population recovery based on pre-disturbance system identity derived from qualitative, historical observations. We document a beginning recovery of the dracaena population in the study area. Around half of the mapped population are individuals in the sapling stage, and they are in good health. Its current realized niche is described by higher altitudes, steeper slopes, more concave landscape forms and east-facing aspects compared to areas where dracaena individuals are absent. However, for the new generation of dracaena saplings we find signs of a leaning range shift where saplings are shifted towards higher altitudes near the mist-influenced escarpment. A full collapse and eventual extirpation of the endangered Dracaena ombet population may at best be averted, or at least delayed in the study area. Our resilience analysis indicates that a full recovery will be a slow process due to the inherent natural climate variability of arid lands, only allowing sporadic regeneration. Considering this species’ information legacy, saplings seem to be well equipped to survive such variability, but perhaps within a restricted safe operating space. Conservation measures should therefore be taken to secure the survival of the new generation along with broader spatial scale studies to confirm whether our findings reflect a regional phenomenon.